Sistem Manajemen Mutu PLTN Dari Perspektif Regulasi Di Indonesia Dan Standar Yang Berlaku - Cusmanri, Fery Putrawan (Jurnal Hukum & Pembangunan, 2020)
Investment in the construction of nuclear power plants is an interesting investment. This is indicated by the emergence of investment plans for the construction of nuclear power plants in Indonesia. Communities and industries that make electricity a primary need will certainly welcome the potential energy offered by nuclear power plants. However, on the other hand the quality of NPP energy services must of course be maximized. This paper was made to provide a brief description of the management system requirements that need to be met by the NPP permit applicant along with additional best practices from the ISO 9001: 2015 standard related to the quality management system and ISO 50001: 2018 related to energy sector management systems. From the results of the analysis by comparing the BAPETEN Chairman Regulation No. 10 Year 2010 about Management System for Facilities and Activities with international standards it was concluded that there are still aspects of international standards that have not been met in regulations in Indonesia, such as supply chain management, inappropriate product control, continuous improvement, and communication with consumers. This can be a consideration for the preparation of further regulation.